Influence of micro additives on printing and electric parameters of conductive adhesives for printing electronic applications. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to investigate the influence of different micro additives to new compositions of electrically conductive adhesives (ECA) on their printing properties as well as electric parameters expressed in resistivity of joints cured in low temperatures and obtain recommendations for elaboration of ECA appropriate for printing electronic applications.Design/methodology/approach – The three different types of silver flakes and two types of micro powders were added to basic matrix of ECA to create ECA composition for investigation. The ECA were printed via stencil on elastic substrate creating the special designed samples which next were cured in 25°C, 50°C or 80°C. The SEM with EDS analysis was utilized for assessment of shapes and sizes of the input materials for ECA. The microscopic observation and resistivity measurements of samples by four‐probe method were used for assessment of the influence of ECA compositions on prints quality as well as on electric parameters of adhesives joints.Findings – The results show that the quality of the prints made with the use of elaborated adhesive compositions is related mainly with the amount and type of filler used in ECA. The electrical properties of joints were dependent from type of silver flakes and amount of micro‐additives as well as curing temperature.Research limitations/implications – It is suggested that further studies are necessary for the confirmation of the practical application, especially of the mechanical and reliability properties of the joints obtained with the use of final composition of the elaborated ECA.Originality/value – The presented results of analyses provide information regarding the correlation between the composition of ECA, properties of elements creating them and the results of printing and electric parameters of joints produced of them. It showed positive impact of small carbon micro powder addition both on printing results and resistivity of joints. It pointed out also that the purity of silver components of ECA influences significantly on resistivity of ECA's joints. It is valuable information for ECA's designers as well as end‐users, from the practical point of view.